2016
DOI: 10.1101/lm.043257.116
|View full text |Cite
|
Sign up to set email alerts
|

Subsecond fear discrimination in rats: adult impairment in adolescent heavy alcohol drinkers

Abstract: Discriminating safety from danger must be accurate and rapid. Yet, the rapidity with which fear discrimination emerges remains unknown. Rapid fear discrimination in adulthood may be susceptible to impairment by adolescent heavy alcohol drinking, which increases incidence of anxiety disorders. Rats were given voluntary, adolescent alcohol access, and heavy drinkers were identified. In adulthood, rapid fear discrimination of safety, uncertainty, and danger cues was assessed. Normal rats, but not heavy drinkers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 37 publications
6
27
1
Order By: Relevance
“…As expected, baseline nose poke rates do not differ between trial types. All trial types show the same gradual increase in re- Consistent with our previous results using suppression ratios, measuring rates of nose poking reveals complete discrimination of danger, uncertainty and safey 31,32,39 . Nose poking is reduced to all cues between the first and second sessions, but the emergence of fear discrimination is clearly seen thereafter.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, baseline nose poke rates do not differ between trial types. All trial types show the same gradual increase in re- Consistent with our previous results using suppression ratios, measuring rates of nose poking reveals complete discrimination of danger, uncertainty and safey 31,32,39 . Nose poking is reduced to all cues between the first and second sessions, but the emergence of fear discrimination is clearly seen thereafter.…”
Section: Resultssupporting
confidence: 89%
“…Our laboratory has observed robust danger, uncertainty, and safety discrimination using suppression ratios calcluated from rates of rewarded nose poking 31,32,[35][36][37] . Classic studies examining defensive behaviour have reported robust post shock freezing 18,25,38 .…”
Section: Resultsmentioning
confidence: 99%
“…In the procedure, three auditory cues predict unique foot shock probabilities: danger ( p = 1.00), uncertainty ( p = .375) and safety ( p = .00). Using conditioned suppression of rewarded nose poking as our dependent measure, we have previously found excellent discriminative fear in male and female rats: high to danger, intermediate to uncertainty, and low to safety (Berg et al., ; DiLeo, Wright, & McDannald, ; Ray, Hanlon, & McDannald, ; Walker et al., ; Wright et al., ). Theoretically, +PEs provide an updating mechanism that would permit fear to uncertainty to remain at an intermediate level.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli can be heard or downloaded at http://mcdannaldlab.org/resources/ardbark. Previous studies have found these stimuli to be equally salient, yet highly discriminable (Berg et al, 2014;Wright et al, 2015;DiLeo et al, 2016;Ray et al, 2018). The 42-min pre-exposure sessions consisted of four presentations of each cue (12 total presentations) with a mean inter-trial interval (ITI) of 3.5 min.…”
Section: Pre-exposurementioning
confidence: 99%
“…Drawing from learning theory (Rescorla, 1968), our laboratory has observed rapid scaling of fear to danger, uncertainty and safety in male rats (DiLeo et al, 2016). Present work in our laboratory is aimed at identifying brain regions that permit rapid scaling of fear.…”
Section: Introductionmentioning
confidence: 99%